SPONTANEOUS OCCURRENCE OF Beauveria bassiana VUILL. 1912 (ASCOMYCETES: CLAVICIPITACEAE) ON Thaumastocoris peregrinus (HEMIPTERA: THAUMASTOCORIDAE) - Lorencetti, Grasielle Adriane Toscan (2017)
Exemplars of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae), insect pest of the genus Eucalyptus, were found dead in the Eucalyptus grandis plantation in the city of Realeza, the southwest region of the state of Paraná, Brazil, with white mycelial growth on the surface of the body. Isolation procedures were performed (in Potato-Dextrose-Agar culture) and identification of the pathogen, whereas the ratio between the microorganism and the insect has been established by Koch's postulate. The fungus through standard procedures, was identified as Beauveria bassiana. In the laboratory testing pathogenicity were performed and caused mortality confirmed in 72.2% of the insects at the concentration of 1.0 x 108 conidia.mL-1 after six days inoculation. Studies on the selection of isolates should be performed and justified by the growing demand of the forest sector in search of control strategies for this insect pest. Thus, was verified that Beauveria bassiana naturally infects Thaumastocoris peregrinus, occurring spontaneously in the Paraná state.